1998
DOI: 10.1258/1357633981931344
|View full text |Cite
|
Sign up to set email alerts
|

Teledermatology—high technology or not?

Abstract: As an alternative to attending a conventional dermatology clinic, patients had a high-resolution conventional photographic image taken by a professional medical photographer. The photographic images were viewed by a dermatologist together with referral details from the general practitioner and any other relevant information from the patient's notes. From the images, a dermatological diagnosis was derived and a management plan for each patient instituted. After treatment, histological assessment of the tumours … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
34
0
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(37 citation statements)
references
References 4 publications
2
34
0
1
Order By: Relevance
“…The advantages of teledermatology are a reduction in the number of referrals up to 51%, [78,79,88,89] and the educational value for GPs [78,90]. Furthermore, the recommendations given via teledermatology are simple to implement [91] and both patients and doctors are satisfied with teledermatology [78,90,92,93]. The disadvantages of teledermatology are an extension of the overall time for consultation [91,94].…”
Section: Teledermatology and Teledermoscopymentioning
confidence: 99%
See 1 more Smart Citation
“…The advantages of teledermatology are a reduction in the number of referrals up to 51%, [78,79,88,89] and the educational value for GPs [78,90]. Furthermore, the recommendations given via teledermatology are simple to implement [91] and both patients and doctors are satisfied with teledermatology [78,90,92,93]. The disadvantages of teledermatology are an extension of the overall time for consultation [91,94].…”
Section: Teledermatology and Teledermoscopymentioning
confidence: 99%
“…In the Netherlands, pigmented lesions are considered less suitable for examination by teledermatology [98]. And, although several studies have shown the utility of teledermatology for pigmented lesions [79,80,86,92,93,99,100], in one study almost 20% of the melanomas would have been mismanaged by teledermatology [101]. Furthermore, the effectiveness and efficiency of teledermatology for suspicious skin lesions have been questioned, as a high proportion of the patients still need a face-to-face consultation [102,103].…”
Section: Teledermatology and Teledermoscopymentioning
confidence: 99%
“…The efficacy of teledermatology-dermatologists consulting on cases presented via videoconferencing or electronically transmitted digitized images-is now being explored as a means to make consultation by dermatolo- gists more accessible and cost-effective. 12,13 The use of teledermatology may complement our decision support software, which is intended to help primary care physicians make better decisions about when to consult with dermatologists. The decision support software developed in this study is intended to ultimately serve as a decision-making aid and a teaching tool.…”
Section: Discussionmentioning
confidence: 99%
“…Die Akzeptanz der telemedizinischen Konsultationen ist bei den Patienten und Dermatologen im Allgemeinen sehr hoch [2,16,25]. Das Beurteilen einer solitären Läsion wird oftmals als einfacher angesehen als das disseminierter Hautveränderungen.…”
Section: Teledermatologieunclassified